Construct validation of mobile learning dimension structure: higher learning students’ perspectives - Syed Hassan, Sharifah Sariah; Landani, Zahra Mardani (Zes Rokman Resources, 2016)
This study aimed to validate the mobile learning constructs from a survey of Higher Learning students in two selected Malaysian Universities. Underpinning the framework of Connectivism theory by Siemens and Technology Acceptance Model (TAM) by Davis, 215 undergraduate and postgraduate students responded to the questionnaires. The items of the questionnaire were subjected to validation (face, content, construct). Principal component analysis (PCA) has been employed to determine the underlying dimension structure. All the six hypothesized constructs were retained namely; Mobile learning (the actual use of smartphone in learning), technology competency, technology reliance, ethics, attitude in using smartphone and social wellbeing. The constructs were further confirmed via Confirmatory factor analysis. Technology reliance and competence were not profound to be included in the model. The implications of the study provides a benchmark of empirical evidence and validated questionnaire use for future research.